Modelling of quantum yields in photocatalytic membrane reactors immobilising titanium dioxide - Ignazio Renato Bellobono; Giulia de Martini; Paola Maria Tozzi; Carmen Canevali; Franca Morazzoni; Roberto Scotti; Riccardo Bianchi (International Journal of Photoenergy)
For some model molecules (methanoic and ethanoic acids, methane, and phenol), systematic investigations of quantum yields were carried out in the present paper, as a function of concentration and of absorbed radiant power. Quantum yields Φ∞, calculated from rates, followed an apparently Langmuirian function of initial concentration C0, by which Φ∞ values at “infinite” concentration could be obtained. By having thus established that quantum yields of photomineralisation Φ∞ are independent of radiation wavelength, within the absorption range of semiconductor, but depend on radiant power, such a dependency was experimentally investigated. For all the investigated molecules, the maximum allowable values reached in the low radiant power range clearly appeared as a plateau. On the contrary, at high radiant power values, another plateau, at a value of about 1/4-1/5 with respect to the maximum value, was evident. This was interpreted on the basis of a competition kinetics of hydroxyl radicals with themselves, leading to hydrogen peroxide formation, other than with substrate or intermediate molecules leading to full mineralisation. Modelling of quantum yields as a function of concentration and radiant power thus allows a fully consistent and trustworthy design of photoreactors.